Studies on total phenolics, total flavonoids and antimicrobial activity from the leaves crude extracts of neem traditionally used for the treatment of cough and nausea - Hoda Salim Khamis Al-Jadidi; Mohammad Amzad Hossain (Beni-Suef University Journal of Basic and Applied Sciences, 2015)
The objective of this work is to prepare different crude extracts from the leaves of neem through maceration method and determine their total phenolics, flavonoids and antimicrobial activity by established methods. The different crude extracts were prepared solvents by maceration method using solvents of different polarities. Total phenolics and total flavonoids contents were determined by using UV–visible spectroscopy method. The antimicrobial activity of different crude extracts from the leaves of neem was determined by disc diffusion method against food borne pathogenic bacterial strains Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa) and Vulgaris. Amoxicillin was used as a positive control. The content of total phenolics of different leaves crude extracts was in the range of 20.80–107.29 mg/100 g of powder crude extracts. The content of total flavonoids of different leaves crude extracts was in the range of 61.50–529.50 mg/100 g powder samples. All crude extracts from neem by maceration method at different working concentrations did not show any potential antimicrobial activity. In conclusion, our results of all crude extracts prepared by solvents of different polarities do not support their use as medicine for treating cough and nausea due to high content of total phenolics and flavonoids.